What are the outcomes of the Toddler Talk intervention program which considers the phonological characteristics of target words? : a thesis presented as fulfilment of the requirements for the degree Master of Speech and Language Therapy at Massey University - Court, Samantha (Massey University, 2023)
The Early Language in Victoria Study (ELVS) identified that 19.7% of two-year-old children are late to acquire their first words (Reilly et al., 2009). These children are said to have Late Language Emergence (LLE), whereby they experience delayed onset of language development in the absence of any underlying aetiology (American Speech-Language-Hearing Association, 2023b). Presently, it is difficult for researchers and clinicians alike to predict which children will have no identifiable language difficulties at 5 years of age and which children will experience persistent difficulties in the acquisition of language (Dale et al., 2003; Reilly et al., 2009). Having effective intervention approaches is essential for the 19.7% of two-year-old children who could present to speech and language therapy services for the treatment of LLE. Research has shown a correlation between language and phonological delays, with toddlers who present with LLE also demonstrating restricted syllable structures and reduced phonemic inventories, characteristic of a phonological delay (Fasolo et al., 2008). However, the clinical guidelines for Speech and Language Therapists (SLTs) on early intervention approaches that address this co-occurring phonological delay are non-existent at present (American Speech-Language-Hearing Association, 2023b). This is not surprising as research in this field is scarce, with only two preliminary studies completed to date (Kaiser et al., 2017; Philp et al., 2021).
Keywords: 470402 Child language acquisition